Publicidad mediática. Acercamiento a la relación publicidad e ideología - Toro Tamayo , Luis Carlos (Mediaciones Sociales, 2008)
The mass media have considerably influenced the history of mankind. A study on its implications, as a social mediation ideological machine, must be a reason for constant reflection by social investigators of communication and language. There-fore, the following study analyzes, from a multidisciplinary perspective, advertising discourses announcing the arrival of massive communication technologies as radio, television and internet in society.